A Fixed Point Approach to the Stability of an Integral Equation Related to the Wave Equation - Soon-Mo Jung (Abstract and Applied Analysis)
We will apply the fixed point method for proving the generalized Hyers-Ulam stability of the integral equation 1/2c∫x-ctx+ctuτ,t0dτ=ux,t which is strongly related to the wave equation.